Marketing Communication Strategy at PADAHALSEKON Thrift Business through Instagram Social Media in Reaching Millennial Generation and Gen Z - Sutinnarto; Setiawan, Muhamad Agung; Khairani , Najmi Rizki (Edusight International Journal of Multidisciplinary Studies, 2025)
The digital era presents new business opportunities for business people, one of which is the thrifting business in various regions. This thrifting business focuses on selling quality used clothing and is in demand by the millennial generation and Gen Z. PADAHALSEKON is a thrift located in Pekalongan city which has 54.2K Followers on Instagram. This research aims to analyze the marketing communication strategy implemented by the PADAHALSEKON thrift business through Instagram social media in reaching the millennial generation and Gen Z. Using a descriptive qualitative approach, data was collected through interviews, observations, and document analysis. The results show that creative content-based marketing strategies, active interaction with audiences, and collaboration with influencers are effective in increasing audience engagement, brand loyalty, and product sales. Millennials and Gen Z are attracted to aesthetically pleasing visual communication styles, relevant product narratives, and sustainability values. Nonetheless, challenges such as market competition and changing social media algorithms need to be overcome to maintain marketing success. This research provides insights for thrift businesses and academics in understanding marketing communication practices that are relevant to the needs of today's digital audience.